Kemiskinan dan Pengentasan Kemiskinan Di Sumatera Barat - Perkasa, Ripho Delzy (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2016)
In this paper the authors restrict the study of poverty and government policies in poverty reduction in West Sumatera. This research method is the study of literature. The findings from the data obtained can be seen that the level of poverty in Sumatera Barat from the years 2005-2010 continued to decline. In 2005 the number of poor people amounted to 482 800 with a percentage of 10.89%. In 2006 the number of poor people in West Sumatera experienced an increase of 550 251 inhabitants with a percentage of 12.51%. In this year poverty level are far greater than what is expected in the amount of 12.07%. Likewise, in 2007 the level of poverty in western Sumatera also incompatible with yag expected by the government in the amount of 11.26%. In this year the number of poor people in West Sumatera amounting to 529 200 with a percentage of 11.90%. In 2008 the number of poor people in West Sumatera has decreased and the level of poverty in West Sumatera is far below that have been targeted by the government at 10,85%. This year the amount of poverty in West Sumatera recorded 477 200 inhabitants with a percentage of 10.67%. So also in 2009 and 2010 the number of poor recorded is also less than the target set by the government.